Методологія сучасного українського конституціоналізму - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2012)
The article contains the structural characteristics of the methodology of Modern Ukrainian Constitutionalism. The author substantiates the four-level structure of the methodology of Modern Ukrainian Constitutionalism: the first level - the dialectical and philosophical, the second level - special, the third level - universal, the fourth level - practical and transformative. It is determined that the methodology of Modern Ukrainian Constitutionalism is based on fundamental principles: anthropology, intelligibility, truth and objectivity of scientific knowledge of constitutionalism, the unity of theory and practice, determinism.
Крусян А. Р. Методологія сучасного українського конституціоналізму / А. Р. Крусян // Юридичний вісник : щоквартальний журнал. - 2012. - №2. - С. 4-12.
Keywords: конституціоналізм; методологія; методи; методологія конституціоналізму; принципи методології конституціоналізму; конституционализм; методология; методы; методология конституционализма; принципы методологии конституционализма; constitutionalism; methodology; methods; methodology constitutionalism; methodological principles of constitutionalism